Analisis Pengaruh Desain "6-Fasa Tak Simetris" 2 Lapis Kumparan Terhadap Efisiensi Motor Induksi 3-Fasa Dengan Menggunakan Metode Elemen Hingga - Mhd Zulfikar Erfani; Zuriman Anthony; Erhaneli Erhaneli; Anggun Anugrah; Arfita Yuana Dewi (Elkom: Jurnal Elektronika dan Komputer, 2024)
This study examines the role of Artificial Intelligence (AI) in marketing strategy through a Systematic Literature Review (SLR) approach. AI has shown a transformative impact by outperforming traditional methods, especially in optimizing big data-based marketing strategies. With the ability to analyze consumer behavior in depth, AI enables businesses to personalize marketing efforts and improve user experiences more efficiently and responsively. However, challenges such as data privacy, high initial investment, and reliance on data quality remain major concerns that must be addressed. This study also evaluates the effectiveness of using AI across marketing channels, which shows significant differences in their impact on business strategy. In addition, the integration of AI-based fitness equipment is considered to have a major contribution in increasing consumer satisfaction while driving online business growth. The results of this study provide valuable insights into the effective implementation of AI, as well as highlight the importance of maintaining data security and implementing AI strategically to provide optimal benefits for consumers and business development.